Modeling the effects of unilateral and uniform emission regulations under shipping company and port competition - Sheng, Dian; Li, Zhi-Chun; Fu, Xiaowen; Gillen, David (Transportation research. Part E, Logistics and transportation review, 2017)
•Model the effects of a unilateral vis-à-vis a uniform maritime emission regulation.•Unilateral regulation may lead to an increase in total emissions.•Uniform regulation always reduces total emissions.•Asymmetric effects on shipping firms and ports can occur under either regulation. This study develops an integrated model to investigate the economic and environmental effects of a unilateral maritime emission regulation vis-à-vis a uniform maritime emission regulation. The proposed model explicitly incorporates the effects of competition between regional ports and between shipping companies, and captures operational considerations such as the inventory costs of in-transit cargo, and the tradeoff between enlarged fleet size and slow steaming. The behaviors of shipping companies and ports are modeled in a two-stage game so that market equilibria under alternative regulations can be solved and compared. The findings suggest that a unilateral regulation may actually lead to an increase in total emissions, whereas a uniform regulation always reduces total emissions. Under either type of regulation, there can be asymmetric effects on shipping companies and ports. Therefore, regulators and the maritime industry need to strike a balance between emission reduction and fair competition. Our study cautions against unilateral regulations, and emphasizes the importance to take into account the effects of alternative emission policies on the operations of shipping companies and ports.